2016
DOI: 10.1038/ncomms12660
|View full text |Cite
|
Sign up to set email alerts
|

Optical patterning of trapped charge in nitrogen-doped diamond

Abstract: The nitrogen-vacancy (NV) centre in diamond is emerging as a promising platform for solid-state quantum information processing and nanoscale metrology. Of interest in these applications is the manipulation of the NV charge, which can be attained by optical excitation. Here, we use two-colour optical microscopy to investigate the dynamics of NV photo-ionization, charge diffusion and trapping in type-1b diamond. We combine fixed-point laser excitation and scanning fluorescence imaging to locally alter the concen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 34 publications
5
63
0
Order By: Relevance
“…The situation is avoided in the current study by exciting and detecting mm 3 volume that is relatively large and the effects from the adjacent crystal will be small. Much smaller spot sizes are more relevant for applications and there is a need to investigate how the present observations are modified when the diffusion of electrons and holes into and out of the detected volume as in [52] becomes significant.…”
Section: Spacialmentioning
confidence: 97%
“…The situation is avoided in the current study by exciting and detecting mm 3 volume that is relatively large and the effects from the adjacent crystal will be small. Much smaller spot sizes are more relevant for applications and there is a need to investigate how the present observations are modified when the diffusion of electrons and holes into and out of the detected volume as in [52] becomes significant.…”
Section: Spacialmentioning
confidence: 97%
“…* rakshyakar.giri@iit.it Attempts to control the charge states of NVs by manipulating the Fermi level are reported in the literature [11,[18][19][20][21][22]. It was demonstrated that an ensemble of NV centers could be stable enough to be used as a charge based data storage medium [23,24]. Other studies on dense ensembles of NVs and near-surface single NVs reported a strong interplay between charge and spin dynamics during illumination as well as in the dark that can interfere with spin measurements [13,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to NV defects, irradiation and post-irradiation annealing can create deep level trap states such as neutral NV centers (NV 0 ), or charged nitrogens (N + ) as well as divacancies [16]. These deeps level trap states influence the photophysics and spin relaxation of NV centers [17][18][19].…”
mentioning
confidence: 99%